2016
DOI: 10.1111/vaa.12305
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of long-term anaesthesia in broiler chickens

Abstract: ObjectiveTo provide stable anaesthesia of long duration in broiler chickens in order to perform a terminal caecal ligated loop procedure.Study designProspective experimental study.AnimalsSeven clinically healthy broiler chickens (Gallus domesticus) aged 27–36 days, weighing 884–2000 g.MethodsAnaesthesia was induced and maintained with isoflurane in oxygen. All birds underwent intermittent positive pressure ventilation for the duration. End‐tidal carbon dioxide, peripheral haemoglobin oxygen saturation, heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The supernatants were collected, filtered through a 0.22-μm-pore-size syringe filter (Millipore, USA) and inoculated into 7-day-old specific pathogen-free (SPF) chicken embryos which were collected from the SPF Experimental Animal Center (Wens Dahuanong Biotechnology Co., Ltd., Guangdong, China) as previously described [18]. All animals used in this study were unconscious and anaesthesia was maintained with isoflurane in oxygen, and then euthanized by parenteral pentobarbitone at the end of experiment as previously described [20]. Animal experiments were approved by local institutional ethical committee to conduct experiments in chicken embryo and poultry birds as per ethical requirement.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants were collected, filtered through a 0.22-μm-pore-size syringe filter (Millipore, USA) and inoculated into 7-day-old specific pathogen-free (SPF) chicken embryos which were collected from the SPF Experimental Animal Center (Wens Dahuanong Biotechnology Co., Ltd., Guangdong, China) as previously described [18]. All animals used in this study were unconscious and anaesthesia was maintained with isoflurane in oxygen, and then euthanized by parenteral pentobarbitone at the end of experiment as previously described [20]. Animal experiments were approved by local institutional ethical committee to conduct experiments in chicken embryo and poultry birds as per ethical requirement.…”
Section: Methodsmentioning
confidence: 99%
“…Found in medicinal plants, including anemones, it stimulates beta cells in the liver to increase insulin secretion to reduce glucose formed during stress [29], [30]. The lungs to the cells of the body and carbon dioxide from the cells of the body to the lungs, thus maintaining the ratio of PCV, Hb and hemoglobin is important in transporting and supplying oxygen for cellular respiration [31], and this is noted in Table (1,2) and it is noted that the percentage of total protein, albumin and globulin is maintained higher than the two control treatments. These results agree with [32], [33] where they indicated that medicinal plants preserve proteins.…”
Section: Discussionmentioning
confidence: 99%
“…On day 15, 3 broilers from each cage were randomly selected (9 broilers from 3 cages for each treatment) for the collection of samples to evaluate the effect of gEGF on their immune function and intestinal development. Blood was collected from the wing vein of all randomly selected broilers before they were anaesthetized according to O’Kane’s method [ 27 ] and sacrificed by exsanguinations for the sample collection of intestinal tissues and immune organs. Care and maintenance of all animals were in line with the Guide for the Care and Use of Laboratory Animals Monitoring Committee of Hubei Province, China.…”
Section: Methodsmentioning
confidence: 99%